Management of recurrent fracture of central incisor with internal resorption using light transmitting (luminex) post - Hariharan V; Nandlal B; Srilatha K (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2010)
The normal root canal anatomy may be altered in various pathological processes and making it very difficult and at times impossible to achieve ideal obturation by normal methods. Internal resorption is one among them. There are several treatment protocols advised for this pathological condition. A crown-root fracture is defined as a fracture involving enamel, dentin and cementum and accounts for 5% of all traumatic injuries to the permanent dentition. In anterior teeth, these fractures are usually caused by direct trauma and often complicated in fully erupted teeth. In cases where the fracture line extends down along the long axis of the root, extraction of the tooth is indicated. The purpose of this report is to present the use of light transmitting post system to reinforce the crown root fractured maxillary central incisor due to trauma and internal resorption.